Investigating the Perovskite Ag1-3xLaxNbO3 as a High-Rate Negative Electrode for Li-Ion Batteries - Le Calvez, Etienne; Espinosa-Angeles, Julio César; Whang, Grace J.; Dupré, Nicolas; Dunn, Bruce S.; Crosnier, Olivier; Brousse, Thierry (Frontiers in Chemistry, 2022)
Graphical Abstract